LEGAL PROTECTION FOR GOOD FAITH LAND BUYERS IN LEASE AGREEMENTS WITH FOREIGN NATIONALS - Richard (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study aims to determine and analyze the legal protection for good faith land buyers who enter into lease agreements with foreign nationals. The theoretical framework of this research uses the theory of legal protection, the theory of good faith purchaser, and the theory of agreement. The research methodology used is normative juridical legal research, focusing on library materials consisting of primary and secondary sources such as legal regulations, books, theses, and journals related to this research. The legal protection of foreign nationals who conduct land leasing transactions in Indonesia is basically regulated in the Basic Agrarian Law (UUPA) Number 5 of 1960 and other related regulations. According to the UUPA, foreign nationals are not allowed to own land in Indonesia they may have the right of use or the right of lease. This research highlights the importance of legal protection for good faith buyers in such transactions, to ensure their protection under the law. The practical and theoretical implications of this research provide insight into how the results of this study may be applied or influence practice in the field of property law, particularly in international land lease agreements. These implications may affect legal practitioners, policy makers, and foreign investors involved in the Indonesian real estate sector. This research contributes to the literature by exploring the legal complexities surrounding land transactions involving foreign nationals and good faith buyers. The originality of this research lies in the in-depth analysis of the interplay between national land laws and international lease agreements of both legal practitioners and buyers regarding the legal protections available in such transactions.